A comparative study of three bone age assessment methods on Chinese preschool-aged children - Gao, Chengcheng; Qian, Qi; Li, Yangsheng; Xing, Xiaowei; He, Xiao; Lin, Min; Ding, Zhongxiang (Frontiers in Pediatrics, 2022)
Abstract Background: Bone age assessment (BAA) is an essential feature in the clinic. Three major BAA methods, Greulich–Pyle (GP), Tanner–Whitehouse 3 (TW3), and China 05 RUS–CHN (RUS–CHN), were applied to comprehensively compare bone age (BA) and chronological age (CA) in a Chinese sample of preschool children. This study was designed to determine the most reliable method. Methods: The BAA sample consisted of 207 females and 183 males aged 3–6 years from the Zhejiang Province in China. The radiographs were estimated according to the GP, TW3, and RUS–CHN methods by two pediatric radiologists. The data were analyzed statistically using boxplots, the Wilcoxon rank test, and Student’s t-test to explore the difference (D) between BA and CA. Results: According to the distributions of D, the boxplots showed that the median D of the TW3 method was close to zero for both male and female subjects. The TW3 and RUS–CHN methods tended to overestimate the age of both genders. The TW3 method had the highest classification rate for males and a similar rate for females. The results of the two hypothesis tests did not show any significant differences between the BA and CA when the GP method was applied to 3-year-old males and 4-year-old females. The TW3 method showed similar results when applied to 6-year-old females. The RUS–CHN method showed the worst results among the three methods. Conclusion: The TW3 method was superior to the GP and RUS–CHN methods but not reliable on its own. A precise age diagnosis for preschool children cannot be easily made if only one of the methods is available. Therefore, it is advantageous to combine multiple methods when applying BAA clinically.